Evaluation and Clinical Validity of a New Questionnaire for Mikulicz's Disease. (8th May 2012) - Yamamoto, Motohisa; Takahashi, Hiroki; Ishigami, Keisuke; Yajima, Hidetaka; Shimizu, Yui; Tabeya, Tetsuya; Matsui, Mikiko; Suzuki, Chisako; Naishiro, Yasuyoshi; Yamamoto, Hiroyuki; Imai, Kohzoh; Shinomura, Yasuhisa
Abstract : Objectives . The characteristic features of Mikulicz's disease (MD) are diffuse enlargement of the lacrimal and submandibular glands, elevated levels of serum immunoglobulin (Ig)G4, and abundant infiltration of IgG4-positive plasmacytes into both glands. No disease index is available to properly evaluate MD, so we developed a functional assessment of MD, the Mikulicz's disease activity questionnaire (MAQ), and evaluated its clinical efficacy. Methods . We selected 18 patients who were either being treated for MD or who had presented with recurrence. The patients completed a self-assessment and were scored according to the MAQ sheet during each visit between December 2009 and August 2011. Assessment items were in regard to increases or decreases in lacrimal and salivary gland enlargement and severity of sicca symptoms. Results . On the first visits, MAQ scores were high, but scores decreased rapidly as treatment progressed. When doses of glucocorticoid were reduced, some patients showed increased scores. Dry-symptom scores increased initially. MAQ scores for patients with recurrent MD gradually increased over several months before relapse. However, some patients displayed no elevation in MAQ scores due to relapses at other sites. Conclusion . MAQ score can be used to quantify flares and treatment response and is useful for functional assessment of MD.